1986
DOI: 10.1084/jem.164.5.1809
|View full text |Cite
|
Sign up to set email alerts
|

Human rheumatoid factor crossidiotypes. I. WA and BLA are heat-labile conformational antigens requiring both heavy and light chains.

Abstract: Three human monoclonal rheumatoid factor (mRF) crossidiotype (XId) groups, WA, PO, and BLA, were defined using polyclonal antisera (1, 2) . Both the WA and the BLA XIds appeared to be associated with the antigen-combining site (2), and serologic studies (3, 4) indicated that the antisera defining the WA XId appeared to recognize a determinant requiring both H and L chains . Structural characterization of the Ids was not done. Extensive studies (5-7) have recently been performed, however, to determine the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 9 publications
(6 reference statements)
1
23
0
Order By: Relevance
“…5) and most likely account for the difference in the antigen binding characteristics, -as well as the observed differences in the expression of idiotype. This difference lends further support to the importance ofthe D-J4 region (22,25,58) ofthe RFs, both for expression of the Wa idiotype and for antigen binding. Until other related anti-CMV antibodies with the same specificity are described, no firm conclusions about the importance of parts of the variable regions to anti-CMV activity can be made.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…5) and most likely account for the difference in the antigen binding characteristics, -as well as the observed differences in the expression of idiotype. This difference lends further support to the importance ofthe D-J4 region (22,25,58) ofthe RFs, both for expression of the Wa idiotype and for antigen binding. Until other related anti-CMV antibodies with the same specificity are described, no firm conclusions about the importance of parts of the variable regions to anti-CMV activity can be made.…”
Section: Discussionmentioning
confidence: 77%
“…The Wa idiotypic family, representing -60% of monoclonal RFs, has been found to be highly restricted in the use of light and heavy chain variable region gene segments (20)(21)(22)(23)(24)(25)(26)(27)(28). This is analogous to the restricted use of immunoglobulin variable region gene segments in murine antigen specific systems, many of which bear cross-reactive idiotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid sequence showed that two CRI-positive RFs have homologous light chains, but not heavy chains [4]. Recently, the expression of the "Wa" CRI has been reported to be conformation dependent [2]. Kunkel and co-workers also described another CRI on 20 % of the RFs, termed the minor "Po" CRI [28].…”
Section: Cri Expression By Human Rf Kappa Light Chainsmentioning
confidence: 96%
“…The peak of HCV present in the void volume was contaminated with small amounts of immunoglobulins that were removed by using immobilized rProtein A (Repligen). Immoblotting (dot blots) to detect small amounts of protein was performed as described (7). Sensitivity of the assay was 100 pg for IgG and IgM and 200 pg for apolipoproteins B and E. Lipoproteins were quantitated by Lowry This paper was submitted directly (Track II) to the PNAS office.…”
Section: Methodsmentioning
confidence: 99%